2010
DOI: 10.1186/1741-7007-8-138
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein regulators EGL-10 and EAT-16, the Giα GOA-1 and the Gqα EGL-30 modulate the response of the C. elegansASH polymodal nociceptive sensory neurons to repellents

Abstract: BackgroundPolymodal, nociceptive sensory neurons are key cellular elements of the way animals sense aversive and painful stimuli. In Caenorhabditis elegans, the polymodal nociceptive ASH sensory neurons detect aversive stimuli and release glutamate to generate avoidance responses. They are thus useful models for the nociceptive neurons of mammals. While several molecules affecting signal generation and transduction in ASH have been identified, less is known about transmission of the signal from ASH to downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In response to quinine, a transient rise in intracellular calcium levels has been seen in the ASHs of wild-type animals [8], [17], [65]. We imaged quinine-evoked calcium fluxes in wild-type, egl-4(lof) and egl-4(gof) animals expressing G-CaMP3 in ASH ( sra-6p::G-CaMP3 ) [69], [70].…”
Section: Resultsmentioning
confidence: 99%
“…In response to quinine, a transient rise in intracellular calcium levels has been seen in the ASHs of wild-type animals [8], [17], [65]. We imaged quinine-evoked calcium fluxes in wild-type, egl-4(lof) and egl-4(gof) animals expressing G-CaMP3 in ASH ( sra-6p::G-CaMP3 ) [69], [70].…”
Section: Resultsmentioning
confidence: 99%
“…Although the C. elegans G␣ q/11 ortholog EGL-30 contributes to the modulation of ASH-mediated sensory signaling, the G␣ subunits ODR-3 and GPA-3, which are more similar to the G␣ i/o family, predominantly transduce ASH chemosensory signals (3,(42)(43)(44). We found that changing RH domain residues in Ce-GRK-2 that correspond to residues shown to mediate interaction between mammalian GRK2 and G␣ q/11 did not disrupt the ability of Ce-GRK-2 to restore ASH-mediated chemosensory behaviors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ASH sensory neurons rely mainly upon two stimulatory G␣s, ODR-3 and GPA-3, which are both most similar to the G␣ i/o family, to mediate aversion (3,(42)(43)(44)(45). EGL-30 is the single C. elegans G␣ q/11 ortholog, and it serves a modulatory role in aversive signaling (43).…”
Section: Rh Domain-mediated Interactions Are Not Required For Ce-grk-mentioning
confidence: 99%
See 1 more Smart Citation
“…The feeding state of the animal affects release of neurotransmitters that signal onto the ASHs to activate several G proteins that alter ASH function (Wragg et al, 2007; Harris et al, 2009; Harris et al, 2010; Ezak and Ferkey, 2010). Among these, Gα o acts by inhibiting glutamate release from ASHs (Harris et al, 2010; Esposito et al, 2010). We found that the AGS-3is expressed in ASH (Fig.…”
Section: Resultsmentioning
confidence: 99%